2020
DOI: 10.1016/j.sjbs.2020.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Role of brain renin angiotensin system in neurodegeneration: An update

Abstract: a b s t r a c tRenin angiotensin system (RAS) is an endocrine system widely known for its physiological roles in electrolyte homeostasis, body fluid volume regulation and cardiovascular control in peripheral circulation. However, brain RAS is an independent form of RAS expressed locally in the brain, which is known to be involved in brain functions and disorders. There is strong evidence for a major involvement of excessive brain angiotensin converting enzyme (ACE)/Angiotensin II (Ang II)/Angiotensin type-1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 125 publications
1
92
0
3
Order By: Relevance
“…6,11,15 ACE2, the necessary cell surface host receptor for SARS-CoV-2, has been previously shown to be expressed on neurons and found to play a role in neurodegeneration. 41 The TMPRSS2 gene, also required for SARS-CoV-2 infection, has not been well studied in the nervous system although one study in a rat model has described expression of TMPRSS2 in neurons of the central nervous system. 42 Previous studies in mice have shown that after intranasal inoculation, the SARS-CoV-1 virus is neuroinvasive with infection directly transmitted through olfactory neurons into the central nervous system.…”
Section: Olfactory Dysfunction In Covid-19mentioning
confidence: 99%
“…6,11,15 ACE2, the necessary cell surface host receptor for SARS-CoV-2, has been previously shown to be expressed on neurons and found to play a role in neurodegeneration. 41 The TMPRSS2 gene, also required for SARS-CoV-2 infection, has not been well studied in the nervous system although one study in a rat model has described expression of TMPRSS2 in neurons of the central nervous system. 42 Previous studies in mice have shown that after intranasal inoculation, the SARS-CoV-1 virus is neuroinvasive with infection directly transmitted through olfactory neurons into the central nervous system.…”
Section: Olfactory Dysfunction In Covid-19mentioning
confidence: 99%
“…Importantly, there is a RAS in the brain, as well (85). Brain RAS is similar to the other tissue RAS (86). ACE2 has been reported to be expressed specifically in the areas controlling central blood arterial pressure (78).…”
Section: Ace2 a Member Of Brain Ras May Have Cardioprotective And Cmentioning
confidence: 86%
“…In addition, animal model demonstrated that nitric oxide (NO) signaling pathways may also be influenced by ACE2 over-expression in the CNS as demonstrated by an overall reduction of hypertension of neurogenic type in syn-hACE2 mice (78,79,84). Therefore, it has been suggested that since ACE2 possesses a monitoring role in the central regulation of cardiovascular function and blood pressure (86), ACE2 in the brain is a potential therapeutic target for hypertension and other cardiovascular diseases that result from an overactive RAS (80). This fact is significantly crucial in the context of COVID-19 because, apart from pneumonia, COVID-19 leads to acute myocardial injury and, progressively, chronic damage to the cardiovascular system (87).…”
Section: Ace2 a Member Of Brain Ras May Have Cardioprotective And Cmentioning
confidence: 99%
See 2 more Smart Citations